Molecular Mapping of PMR1, a Novel Locus Conferring Resistance to Powdery Mildew in Pepper (Capsicum annuum) - Jo, Jinkwan; Venkatesh, Jelli; Han, Koeun; Lee, Hea-Young; Choi, Gyung Ja; Lee, Hee Jae; Choi, Doil; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2017)
Powdery mildew caused by Leveillula taurica is a major fungal disease of greenhouse-grown pepper (Capsicum annuum). Powdery mildew resistance has a complex mode of inheritance. In the present study, we investigated a novel powdery mildew resistance locus, PMR1, using two mapping populations, 102 ‘VK515’ F2:3 families (derived from a cross between resistant parental line ‘VK515R’ and susceptible parental line ‘VK515S’) and 80 ‘PM Singang’ F2 population (derived from the F1 ‘PM Singang’ commercial hybrid). Genetic analysis of the F2:3 ‘VK515’ and F2 ‘PM Singang’ mapping populations revealed a single dominant locus inheritance of the powdery mildew resistance trait. Genetic mapping showed that the PMR1 locus is located on syntenic regions of pepper chromosome 4 in a 4-Mb region between markers CZ2_11628 and HRM4.1.6 in ‘VK515R’. Six molecular markers including one SCAR marker and five SNP markers were localized to a region 0 cM from the PMR1 locus. Two putative nucleotide-binding site leucine-rich repeat (NBS-LRR)-type disease resistance genes were identified from the PMR1 region. Genotyping-by-sequencing (GBS) and genetic mapping analysis revealed a suppressed recombination in the PMR1 region perhaps due to alien introgression. In addition, a comparison of species-specific InDel markers as well as GBS-derived SNP markers indicated that C. baccatum represents a possible source of alien introgression of powdery mildew resistance into ‘VK515R’. The molecular markers developed in this study will be especially helpful for marker-assisted selection in pepper breeding programs for powdery mildew resistance.